Didacticism work in the “Christian garden” by Jakub Lubelczyk - Polanin, Żaneta (Melusine. Old Literature and Culture, 2026)
The article is based on the analysis of the way that didacticism works in the “Christian garden” (“Wirydarz krześcijański”) by Jakub Lubelczyk (1530–1563). The paper focuses primarily on the characteristics of the main character (Krześcijanin) and his spiritual transformation, which is the result of a conversation with the guides. The next stages of the Krześcijanin development have shown the persuasion, which was used by the author through deliberative rhetoric (genus deliberativum), encouraging (suasio), and discouraging (dissuasio) statements. Lubelczyk articulates his arguments based on the Holy Bible, moral guidelines and ideas created from a perspective of the Reformation movement. “Christian garden” was juxtaposed with the selected literary works of Mikołaj Rej, which show that the rhetorical measures used by Lubelczyk for didactic purposes were also used by other artists.